Impact of melphalan dose during reduced‐intensity conditioning on engraftment of cord blood transplantation for chronic Epstein‐Barr virus‐associated T or NK cell lymphoproliferative diseases. Issue 9 (21st June 2020) - Mayumi, Azusa; Sawada, Akihisa; Sato, Maho; Shimizu, Mariko; Ioi, Aya; Higuchi, Kohei; Yasui, Masahiro; Kawa, Keisei; Inoue, Masami
Abstract: The rejection rate in cord blood transplants for chronic Epstein‐Bar virus‐associated T or natural killer cell lymphoproliferative diseases using our standard reduced‐intensity conditioning "LPAM140 regimen, " which includes fludarabine, melphalan (LPAM), etoposide, and antithymocyte globulin, has been high. To ensure better engraftment, we increased the LPAM dose to 210 mg/m 2 ("LPAM210 regimen"). Patient data (n = 22; LPAM140, n = 7; LPAM210, n = 15) were analyzed retrospectively. The engraftment rate after the LPAM210 regimen (100.0%) was significantly higher than that after the LPAM140 regimen (57.1%; P = .002). Fludarabine combined with melphalan (210 mg/m 2 ) had a favorable impact on engraftment.